Effect of a Low Dose of Carvedilol on Cyclophosphamide-Induced Urinary Toxicity in Rats-A Comparison with Mesna - Anna Merwid-Ląd; Piotr Ziółkowski; Marta Szandruk-Bender; Agnieszka Matuszewska; Adam Szeląg; Małgorzata Trocha (MDPI AG, 2021)
One of the major side effects of cyclophosphamide (CPX)-an alkylating anticancer drug that is still clinically used-is urotoxicity with hemorrhagic cystitis. The present study was designed to evaluate the ability of carvedilol to protect rats from cyclophosphamide-induced urotoxicity. Rats were injected intraperitoneally (i.p.) with CPX (200 mg/kg) and administered carvedilol (2 mg/kg) intragastrically a day before, at the day and a day after a single i.p. injection of CPX, with or without mesna (40, 80, and 80 mg/kg i.p. 20 min before, 4 h and 8 h after CPX administration, respectively). Pretreatment with carvedilol partly prevented the CPX-induced increase in urinary bladder and kidney index, and completely protects from CPX-evoked alterations in serum potassium and creatinine level, but did not prevent histological alterations in the urinary bladder and hematuria. However, carvedilol administration resulted in significant restoration of kidney glutathione (GSH) level and a decrease in kidney interleukin 1β (IL-1β) and plasma asymmetric dimethylarginine (ADMA) concentrations. Not only did mesna improve kidney function, but it also completely reversed histological abnormalities in bladders and prevented hematuria. In most cases, no significant interaction of carvedilol with mesna was observed, although the effect of both drugs together was better than mesna given alone regarding plasma ADMA level and kidney IL-1β concentration. In conclusion, carvedilol did not counteract the injury caused in the urinary bladders but restored kidney function, presumably via its antioxidant and anti-inflammatory properties.